Pengaruh Model Pembelajaran Inkuiri Berbantuan Laboratorium Virtual Terhadap Pemecahan Masalah Fisika Peserta Didik - Mahesti Kusdiastuti; Ahmad Harjono; Hairunnisyah Sahidu; Gunawan Gunawan (Indonesian, 2022)
Problem-solving ability is one of the essential competencies that students should develop in physics learning. However, teacher-centered instruction and the limited implementation of laboratory activities have hindered the optimal development of this ability. One alternative to overcome this problem is the implementation of an inquiry learning model assisted by a virtual laboratory. This study aimed to analyze the effect of the inquiry learning model assisted by a virtual laboratory on students' physics problem-solving ability. This study employed an experimental research design using a pretest-posttest control group design. The population consisted of all tenth-grade students of MA DI Putri Nurul Hakim Kediri in the 2015/2016 academic year, while the sample was selected using the cluster random sampling technique. Data were collected using an expert-validated essay test of problem-solving ability. The data were analyzed using normality and homogeneity tests, followed by a pooled variance t-test. The results showed that the experimental group obtained a higher mean posttest score (73.67) than the control group (58.47). Furthermore, the hypothesis testing revealed that tcalculated = 4.469 was greater than ttable = 2.032 at the 5% significance level, indicating that the inquiry learning model assisted by a virtual laboratory had a significant positive effect on students' physics problem-solving ability. Therefore, this learning model can be considered an effective instructional alternative for improving students' physics problem-solving ability.